2011
DOI: 10.2174/138161211795164202
|View full text |Cite
|
Sign up to set email alerts
|

The gp130 Receptor Cytokine Family: Regulators of Adipocyte Development and Function

Abstract: Gp130 cytokines are involved in the regulation of numerous biological processes, including hematopoiesis, immune response, inflammation, cardiovascular action, and neuronal survival. These cytokines share glycoprotein 130 as a common signal transducer in their receptor complex and typically activate STAT3. Most gp130 cytokines have paracrine or endocrine actions, and their levels can be measured in circulation in rodents and humans. In recent years, various laboratories have conducted studies to demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 121 publications
3
58
0
Order By: Relevance
“…The current findings suggest that the IL-6 signaling-mediated increase in lipolysis is restricted to the portally drained mesenteric AT depot because depletion of gp130, the common signal transducer of IL-6, reduced FFA release only from isolated mesenteric but not from epididymal adipocytes. Because IL-6 is the gp130 cytokine with the best-known lipolytic function (9), this finding may be explained by an increased sensitivity of mesenteric adipocytes to IL-6-mediated lipolysis. However, IL-6-induced FFA release was only slightly elevated in mesenteric compared with epididymal adipocytes isolated from wild-type mice (1.25 6 0.14-fold in mesenteric vs. 1.12 6 0.02-fold in epididymal, P = 0.4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current findings suggest that the IL-6 signaling-mediated increase in lipolysis is restricted to the portally drained mesenteric AT depot because depletion of gp130, the common signal transducer of IL-6, reduced FFA release only from isolated mesenteric but not from epididymal adipocytes. Because IL-6 is the gp130 cytokine with the best-known lipolytic function (9), this finding may be explained by an increased sensitivity of mesenteric adipocytes to IL-6-mediated lipolysis. However, IL-6-induced FFA release was only slightly elevated in mesenteric compared with epididymal adipocytes isolated from wild-type mice (1.25 6 0.14-fold in mesenteric vs. 1.12 6 0.02-fold in epididymal, P = 0.4).…”
Section: Discussionmentioning
confidence: 99%
“…Several IL-6 cytokines were shown to individually affect differentiation and adipogenesis, rendering gp130 a potential therapeutic target to combat obesity and its associated diseases (9). Accordingly, it was recently shown that blocking IL-6 transsignaling using a soluble gp130 Fc protein reduces obesityinduced infiltration of macrophages into AT (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Interleukin-6 is considered to be an important inflammatory cytokine, specifically in autoimmune diseases, such as experimental autoimmune encephalomyelitis and rheumatoid arthritis. 41,42 This property may indicate the molecular pathway used by ES to upregulate the molecules observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…CT-1 has been shown to regenerate cirrhotic livers and to improve steatosis in non-alcoholic fatty liver disease (NAFLD) (López-Yoldi et al, 2015). At least the three cytokines neuropoietin (NP), IL-11 and OSM have been shown to inhibit adipocyte differentiation (White and Stephens, 2011).…”
Section: Metabolic Actions Of Gp130 Ligandsmentioning
confidence: 99%